Hubungan antara Pengasuhan Orang Tua dengan Perilaku Agresif Remaja di Jorong Alahan Panjang Kabupaten Solok - Wiwi Rahayu; Syafruddin Wahid (Universitas Negeri Padang, 2018)
This research is motivated by quite high aggressive behavior in Jorong Alahan Panjang Kabupaten Solok. This study aims to find parenting levels, aggressive behavior of adolescents, and the relationship between Parenting Parenting with Aggressive Behavior teenagers in Jorong Alahan Panjang Solok District. This type of research is quantitative correlational. The population in this study amounted to 74 people. The number of samples in this study amounted to 37 people taken 50% of the population using Cluster Random Sampling technique. Data collection techniques are questionnaires, and data collection tools sheets of statements. Data analysis techniques using the formula percentage and Product Moment. The results of the study found that parenting in Jorong Alahan Panjang Solok District is in the less good category, Aggressive Behavior of adolescents are in high enough category, and there is a significant relationship between Parenting Parenting with Aggressive Behavior of adolescents in Jorong Alahan Panjang Solok District.Keywords: Parenting, Aggressive Behavior